Tiktok and Political Communication of Youth: A Systematic Review - Hindarto, Isni Hindriaty (Jurnal Review Politik, 2022)
This research systematically reviewed 30 Scopus indexed journal articles from several countries, with a focus on youth political communication through the TikTok platform.  All articles were published between January 2018 – July 2022 along with the rapid growth of TikTok as the most popular social media, and some overseas political activities that took advantage of the unique and superior features of TikTok. Through a qualitative and quantitative approach, the researcher found a significant increase of youth interest in political practices that are presented in 15-second videos. This study aims to provide learning materials of political communication through TikTok application and pave the way for politicians to engage more youth participation. Recommendations for future research are provided.